(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper studies about the philosophical concept of Integral Education of Sri Aurobindo and its practice of physical and spiritual aspects in Auroville Schools i.e. Mother International and Mirambika situated at New Delhi. The main objective of this study is to investigate the practice of these two aspects of Sri Aurobindo’s Integral Education in these two Auroville Schools. In this context a total sample of 100 students from age group of 12 to 17 years (50 students of Mother International School and 50 students of Mirambika School) were selected by systematic random method. Critical Ratio was applied in order to study practice of physical and spiritual aspect in Auroville schools. It has been found that there is no significant difference between the Mother International School and Mirambika School in physical aspect and there is significant difference between spiritual aspects of integral education. However, in mean difference, the students of Mother International Schools are superior to Mirambika School in respect of physical aspect of Integral Education. The students of Mirambika School are superior to Mother International School in respect of spirituality aspect of Integral education. Physical and spiritual are two most important aspects of integral education and all schools should organise such activities in schools which encourage development of these two aspects besides mental, vital and psyche. We should impart knowledge according to Integral Education.